De Saussure a Benveniste : um percurso teórico que proporciona uma leitura crítica - Gomes, Catiúcia Carniel (2012)
The purpose of this research is to do a theoretical analysis of the concepts covered by Ferdinand de Saussure - in his courses - which were compiled and published posthumously in the Course in general linguistics. This reflection has a connection with another one that is done in this work: the concepts developed by Émile Benveniste, which were based on the CLG. These theoretical reflections have been done because once Benveniste‟s enunciation theory was studied; it was possible to perceive that it was necessary to study the linguistic origin of his concepts, specially the Saussurean concepts, presented in the CLG. The topic of this research is the proposal of a theoretical and critical reading between these linguists, to identify the theoretical assumptions which they have in common and the ones they don‟t. The aim of this study is to choose theoretical concepts developed by Ferdinand de Saussure and Émile Benveniste, compare them and show how these authors and the people who have read these concepts have perceived them, aiming to deepen these concepts and emphasize their relevance to the study of enunciation. Therefore, this is a descriptive and bibliographical research, with a qualitative approach. The following methodological course, regarding the reading and writing processes, has been done: a) a brief presentation of Ferdinand de Saussure‟s biography; b) the selection of essential concepts and their reflections, for the linguistic study, done by this author and presented in the CLG; c) a brief presentation of Émile Benveniste‟s biography; d) the selection of important reflections done by this author and presented, mainly, in the PLG-I and in the PLG-II; e) at last, a comparison (regarding the similarities and the differences) between the concepts developed by these linguists. These readings were mediated by considerations which have been done by readers of both linguists.